Media Convergence and Implication of Television Digitalization Creates a Change Audience Behavior - Tarmawan, I (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Media creates mass audiences and a strong influence as a social control that shapes media influence seen from the social conditions that occur. Technological developments that have triggered media convergence have given birth to new media which is increasingly difficult to place media as social control. The convergence of media and the implications of digitalization of television on changes in audience behavior are interesting parts to be researched. The research method used is a qualitative descriptive case study with the paradigm of developing media analysis from institutions to formats based on content and form and to audiences based on social constructs. The purpose of this study is to determine whether media convergence affects the mass media during the transition period as an implication of digitalization of television in Indonesia and changes in public behavior. The results show that digital technology has triggered media convergence to create new, easily accessible media. The slow migration of digitalisation caused by various factors and regulations encourages stakeholders to use the internet to create new media, the melting of mass media into a new platform that has a positive impact on changes in audience behavior in easy access to information.